Aeromonas salmonicida subsp. salmonicida Early Infection and Immune Response of Atlantic Cod (Gadus morhua L.) Primary Macrophages - Soto-Dávila, Manuel; Hossain, Ahmed; Chakraborty, Setu; Rise, Matthew L.; Santander, Javier (Frontiers in Immunology, 2019)
In contrast to other teleosts, Atlantic cod (Gadus morhua) has an expanded repertoire of MHC-I and TLR components, but lacks the MHC-II, the invariant chain/CD74, and CD4+ T cell response, essential for production of antibodies and prevention of bacterial infectious diseases. The mechanisms by which G. morhua fight bacterial infections are not well understood. Aeromonas salmonicida subsp. salmonicida is a recurrent pathogen in cultured and wild fish, and has been reported in Atlantic cod. Macrophages are some of the first responders to bacterial infection and the link between innate and adaptive immune response. Here, we evaluated the viability, reactive oxygen species (ROS) production, cell morphology, and gene expression of cod primary macrophages in response to A. salmonicida infection. We found that A. salmonicida infects cod primary macrophages without killing the cod cells. Likewise, infected Atlantic cod macrophages up-regulated key genes involved in the inflammatory response (e.g. IL-1β and IL-8) and bacterial recognition (e.g. BPI/LBP). Nevertheless, our results showed a down-regulation of genes related to antimicrobial peptide and ROS production, suggesting that A. salmonicida utilizes its virulence mechanisms to control and prevent macrophage anti-bacterial activity. Our results also indicate that Atlantic cod has a basal ROS production in non-infected cells, and this was not increased after contact with A. salmonicida. Transmission electron microscopy results showed that A. salmonicida was able to infect the macrophages in a high number, and release outer membrane vesicles (OMV) during intracellular infection. These results suggest that Atlantic cod macrophage innate immunity is able to detect A. salmonicida and trigger an anti-inflammatory response, however A. salmonicida controls the cell immune response to prevent bacterial digestion, during early infection.